PERANCANGAN INFRASTRUKTUR KUNCI PUBLIK DENGAN IMPLEMENTASI PEMBANGUNAN SISTEM UJIAN DARING BERBASIS WEB - hermawan setiawan; Kertanegara, Adek Muhammad Zulkham Ristiawan (Universitas Putera Batam, 2023)
During the Covid-19 pandemic, almost all educational institutions in Indonesia are implementing Distance Learning (PJJ). Like learning in general, in each semester an exam will be held, be it the Midterm Exam or the End of Semester Exam, and of course the exam takes place remotely. This has caused concerns from teachers to their students about the method of distributing exam questions and sending exam answer sheets. In other words, it is difficult for teachers to ensure the safety of the distribution of questions, as well as to carry out endorsements and verifications on the exam answer sheets collected by their students. In this study, the authors built a public key infrastructure implemented in a web-based online exam system with an approach to encryption and digital signatures. Encryption and digital signatures are two commonly used primitive cryptography that can provide security services, such as confidentiality, integrity, and authenticity of messages. It is hoped that with this research, we can find out the implementation of public key infrastructure in the web-based online examination system.